Analisis Pengaruh Net Profit Margin (NPM), Current Ratio (CR) dan Debt to Equity Ratio (DER) Terhadap Dividend Payout Ratio (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Pada Tahun 2015-2017) - Rizky Adhyvian; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract This research was conducted with the aim to analyze the effect of partially Net Profit Margin (NPM), the Current Ratio (CR), Debt to Equity Ratio (DER) of the Dividend Payout Ratio (DPR).The population used in this study are all manufacturing companies listed on the Stock Exchange during the period of 2015 through 2017. The sample selection using purposive sampling method. Based on existing criteria obtained samples of 37 companies. The method used is multiple linear regression analysis with hypothesis testing using t test.The results showed that the Partially Net Profit Margin (NPM) significant positive effect on Dividend Payout Ratio (DPR). Partially Current Ratio (CR) is not significant positive effect on the Dividend Payout Ratio (DPR). Debt to Equity Ratio (DER) partially significant positive effect on Dividend Payout Ratio (DPR). Keywords: Net Profit Margin (NPM), the Current Ratio (CR), Debt to Equity Ratio (DER) and Dividend Payout Ratio (DPR).